(untitled) (Journal of Bangladesh Academy of Sciences, 2019)
A study was carried out in the industrial areas in order to determine the composition of trace elements in dusts deposited at homes, identifying different sources of elements and also for their possible health impacts. A total of 14 deposited dust samples were collected from households near industrial areas of Tangail and Gazipur districts during sampling campaign. Samples were analyzed using X-ray Fluorescence and the highest concentration was observed for Fe whereas the overall rank of the concentrations is Fe>Ca>K>Ti>Zn>Pb>Zr>Sr>Rb>Cu>Y>As>Cr>Ni. The Correlation analysis, enrichment factor and factor analysis indicated that anthropogenic sources especially industrial activity, vehicular emission and household cooking are the main sources of trace elements in the study areas. The non-carcinogenic and carcinogenic health risks indicated that children are more vulnerable for non-carcinogenic effects whereas the values of cancer risk for both the child and adult are below the acceptable limit of European Union. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 47-58, 2019